2018
DOI: 10.1002/cpdd.468
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Correlations From 2 Studies Evaluating Abuse Potential of Hydrocodone Extended‐Release Tablets

Abstract: Pharmacokinetic (PK)/pharmacodynamic (PD) correlations were explored in 2 human abuse potential studies of orally and intranasally administered hydrocodone extended-release (ER) 45 mg in healthy, nondependent opioid users. In a crossover study design, subjects received intact hydrocodone ER, finely milled hydrocodone ER, and hydrocodone powder in solution in the oral study and finely milled hydrocodone ER, hydrocodone powder, and finely milled Zohydro® ER in the intranasal study. Spearman ρ and Pearson r value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“… 5 Several studies reported that the abuse potential of opioids are correlated with the rate of rise of drug plasma concentration. [6] , [7] , [8] , [9] However, concerns remain for unraveling the relationships between PK exposure and clinical abuse potential scores and claims have been made such relationships may be complex and inconsistent considering the subjective nature of PD measures and the wide range of AD technologies. For instance, the Branded Industry Working Group compared chewing of oxycodone capsules under fed state (A) with chewing under fasting state (B) and noted that a higher C max value of oxycodone concentrations was observed under fed state (A) but a lower maximum visual analogue scale score for Take Drug Again was noted in subjects.…”
Section: Introductionmentioning
confidence: 99%
“… 5 Several studies reported that the abuse potential of opioids are correlated with the rate of rise of drug plasma concentration. [6] , [7] , [8] , [9] However, concerns remain for unraveling the relationships between PK exposure and clinical abuse potential scores and claims have been made such relationships may be complex and inconsistent considering the subjective nature of PD measures and the wide range of AD technologies. For instance, the Branded Industry Working Group compared chewing of oxycodone capsules under fed state (A) with chewing under fasting state (B) and noted that a higher C max value of oxycodone concentrations was observed under fed state (A) but a lower maximum visual analogue scale score for Take Drug Again was noted in subjects.…”
Section: Introductionmentioning
confidence: 99%